Sertraline on Obsessive Compulsive Disorders in Indonesia (A Case Study) - Faisal, Muhammad Rais; Algristian , Hafid; Azizah AS, Nur (UNUSA Press, 2022)
Background: Obsessive-compulsive disorder (OCD) was originally believed to be a rare mental illness. However, recent surveys and research have shown that OCD is one of the most common mental disorders. Research in India showed that the treatment of OCD using SSRIs (selective serotonin reuptake inhibitors) is preferred over the tricyclic group. This paper will discuss sertraline as the alternative to clomipramine for OCD. Objective: Clomipramine as the treatment of choice for OCD is no longer included in the Indonesian MIMS index. Recent research suggests sertraline is preferred over clomipramine, and this paper discusses the efficacy of sertraline through a case study. Methods: This study is a retrospective descriptive study on the case of 21-year-old male met the ICD-X criteria of OCD for having unwanted thoughts and repetitive behavior for locking the door and orderly compiling the books. The symptoms developed since he graduated from high school (three years before admission) and got worse since the last year. Sertraline was prescribed in the first place. The patient was routinely monitored during each visit for the next three months. Results: The symptoms improved significantly after routinely taking sertraline for two months. The adverse effects were well-tolerated, such as nausea, headaches, and tachycardia. Psychotherapy was needed to modify the patient’s obsession and to anticipate the risk of personality disorder should be noticed because the disorder appeared at a young age. Conclusion: Sertraline as well as psychotherapy are worthy of consideration as first-line OCD therapy in Indonesia.